2019
DOI: 10.1111/eve.13130
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of a mandibular ameloblastic carcinoma with metastases to the mandibular lymph nodes in a pony

Abstract: A 4-year-old Connemara filly was presented with a rapidly growing oral mass on the right rostrolateral mandible and a right mandibular lymphadenopathy. Radiographs of the rostral mandible revealed a lytic, infiltrative mass consistent with soft tissue and mineralised material, and displacement of tooth 403. A biopsy showed characteristic histopathological features of an ameloblastic carcinoma. Subsequent FNA of the right abnormally firm and enlarged mandibular lymph node confirmed the metastatic spread. Comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Detailed studies investigating cytokeratin and vimentin expression at different stages of odontogenesis demonstrate the transient co-expression of cytokeratin and vimentin intermediate filaments in the external enamel epithelium, internal enamel epithelium (pre-ameloblasts), and stellate reticulum cells of the enamel organ. 9,13 Furthermore, studies have demonstrated this dual expression in ameloblastoma and ameloblastic carcinoma in humans, dogs, and horses, 3,4,[8][9][10]14,22 which likely reflects a recapitulation of the expression pattern of primitive odontogenic tissue (i.e., dental lamina or enamel organ).…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Detailed studies investigating cytokeratin and vimentin expression at different stages of odontogenesis demonstrate the transient co-expression of cytokeratin and vimentin intermediate filaments in the external enamel epithelium, internal enamel epithelium (pre-ameloblasts), and stellate reticulum cells of the enamel organ. 9,13 Furthermore, studies have demonstrated this dual expression in ameloblastoma and ameloblastic carcinoma in humans, dogs, and horses, 3,4,[8][9][10]14,22 which likely reflects a recapitulation of the expression pattern of primitive odontogenic tissue (i.e., dental lamina or enamel organ).…”
mentioning
confidence: 96%
“…5 However, ameloblastic carcinoma is exceedingly rare, is reported uncommonly in humans, 5,21 and only a few cases have been reported in horses, dogs, and a rat. 3,4,8,10,11,14,17,22 In addition to ameloblastoma, a primary differential diagnosis for ameloblastic carcinoma is oral squamous cell carcinoma. These 2 neoplasms can have considerable overlap in gross and histologic features, particularly in poorly differentiated squamous cell carcinomas that may have a spindloid phenotype and scant keratinization.…”
mentioning
confidence: 99%
See 3 more Smart Citations